The Effect of Investment and Human Development Index on Economic Growth In Jember Regency In 2010-2020 - Charismasari Darma Pertiwi (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Economic growth as a process of increasing output over time, becomes an important indicator in measuring the success of a country's development. This research is a correlational study that aims to determine the effect of investment on economic growth in Jember Regency, and the effect of human development index on economic growth in Jember Regency during 2010-2020. The analysis method used multiple linear regression with the Ordinary Least Square (OLS) econometric model with the help of Eview 10. The results of this study show that investment has a positive and insignificant effect on economic growth in Jember Regency while the human development index has a positive and significant effect on economic growth in Jember Regency.